Ocean Thermal Energy Conversion (OTEC) Past, Present, and Progress - Kim, Hyeon-Ju; Kim, Albert S. (2020)
The 21st century is characterized as an era of natural resource depletion, and humanity is faced with several threats due to the lack of food, energy, and water. Climate change and sea-level rise are at unprecedented levels, being phenomena that make predicting the future of ocean resources more complicated. Oceans contain a limitless amount of water with small (but finite) temperature differences from their surfaces to their floors. To advance the utilization of ocean resources, this book readdresses the past achievements, present developments, and future progress of ocean thermal energy, from basic sciences to sociology and cultural aspects.